AVALIAÇÃO DO TEOR DE GORDURA NO LEITE DE VACAS DA RAÇA PANTANEIRA EM FUNÇÃO DOS PROCEDIMENTOS DE AMOSTRAGEM - SOARES, Vitória; FERREIRA, Rodrigo Carvalho; LIMA, pedro Gustavo Loesia; BONATTI, Franscine Kelli Quinhones; LUZ, Dirce Ferreira; OLIVEIRA, Marcus Vinicius Morais (ANAIS DO ENIC, 2017)
-